2010
DOI: 10.1248/cpb.58.521
|View full text |Cite
|
Sign up to set email alerts
|

New Pyrano-Pyrone from Goniothalamus tamirensis Enhances the Proliferation and Differentiation of Osteoblastic MC3T3-E1 Cells

Abstract: The genus Goniothalamus comprises about 160 species of shrubs and trees growing in tropical and subtropical Asia. 1) Many of these species are used for timber, as fiber sources, as mosquito repellant, and most interestingly in folk medicine in several countries. 2,3) Phytochemical studies of Goniothalamus species have led to the isolation and characterization of a large number of styryl-lactones. These can be classified into several main subtypes: styryl-pyrones, furano-pyrones, furano-furones, and pyrano-pyro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
23
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 20 publications
2
23
0
Order By: Relevance
“…Tai et al reported the isolation of phenylpyranopyrones with a bicyclo structure and proposed three conformations, namely, the boat−boat, chair−chair, and boat−chair conformations ( Figure S2, Supporting Information). 15 Additionally, all styrylpyrones isolated from this plant were found to possess a 6S configuration, and their structural similarity suggested a common biogenetic pathway, which implies that the configuration of C-1 in 4−6 (originally C-6 in the isolated styrylpyrones) is S (Table S2, respectively. Thus, the absolute configuration of 4 was suggested as 1S,5S,7R,8R with 4a as the proposed structure ( Figure 3).…”
mentioning
confidence: 88%
See 2 more Smart Citations
“…Tai et al reported the isolation of phenylpyranopyrones with a bicyclo structure and proposed three conformations, namely, the boat−boat, chair−chair, and boat−chair conformations ( Figure S2, Supporting Information). 15 Additionally, all styrylpyrones isolated from this plant were found to possess a 6S configuration, and their structural similarity suggested a common biogenetic pathway, which implies that the configuration of C-1 in 4−6 (originally C-6 in the isolated styrylpyrones) is S (Table S2, respectively. Thus, the absolute configuration of 4 was suggested as 1S,5S,7R,8R with 4a as the proposed structure ( Figure 3).…”
mentioning
confidence: 88%
“…The 1 H and 13 C NMR data (Tables 1 and 2) of 4 were closely related to those of (+)-9-deoxygoniopypyrone. 13,15 However, the spectroscopic data of 5 and 6 were similar to those of 8-epi-9-deoxygoniopypyrone, 15 indicating that 4−6 are diastereomers with some structural differences. The data suggested that the equatorial proton (H-8) in 4 occurrs in an axial position in 5 and 6.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…The coupling constant between H-5 and H-6 is 5.4 Hz, indicating that the dihedral angle is close to 45º, thus establishing H-5 is in equatorial orientation, leading to Rconfiguration. Based on the presented spectral data (Table 1) [3], (-)-ent-goniothalamin oxide 12 [3,7], Parvistone D 13 [3,6], 1S,5S,7R,8S,3-exo,7-endo-(+)-8-epi-9deoxygoniopypyrone 14 [3,8] and parvistone E 15 [3].…”
Section: S-goniothalamin 1 αmentioning
confidence: 99%
“…The HPLC profile of the crude extract ( Figure 2) showed presence of the major component as well as several other minor constituents. From the mass data (Table 2), four more styryllactones were identified as 8-epi-9deoxygoniopypyrone 2 [13], 9-deoxygoniopypyrone 3 [14], digoniodiol 4 [15] and goniothalamin 5 [16]. Goniothalamin has been reported to possess antimalarial activity.…”
mentioning
confidence: 99%